(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article explores the epidemiology of COVID-19, examining transmission dynamics, risk factors, preventive measures, and the effectiveness of vaccines. It discusses the impact of the pandemic on global health systems and makes recommendations for future preparedness.